Optimalisasi Limbah Bawang Merah sebagai Pupuk Cair Organik untuk Budidaya Tanaman Hias Sayur - Nur Hayati; Lina Arifah Fitriyah; Nindha Ayu Berlianti; Noer Af'idah (Jurnal Pemberdayaan Masyarakat, 2022)
The people of Drenges, Kabuh Village, Jombang Regency are one of the producers of red onion. When harvesting, the large amount of red onion waste has not been utilized by the community. According to the results of previous research that has been done, it proves that red onions contain compounds that are beneficial for plant growth. Red onion waste in the form of red onion skin can be used as organic liquid fertilizer. This Community Service Activity (PKM) aims to provide knowledge to the community in the use of red onion waste as organic liquid fertilizer for the growth of ornamental vegetables. The target of this activity is women, totaling 16 people. PKM activities consist of situation analysis, training, mentoring and evaluation stages. The situation analysis was carried out in April 2021, the training activities took place on August 7-8 2021, while the mentoring lasted until September 5, 2021. The results of this activity were participant participation which reached 100%; as many as 81.25% active participants and have understood the training material; and 87.5% of participants were able to make liquid fertilizer from onion waste.